Numerical Simulation of Heat Generation During Plunging Stage in Orbital Friction Stir Welding on Pipe Aluminum Alloys AA6061-T6 Adapting a Pure Lagrangian Formulation - Ahmad, K. (Springer Science and Business Media Deutschland GmbH, 2022)
Friction stir welding consists of three operation stages operation beginning with plunging, pre-heating (dwelling) and welding along the joint. Each stage has its own functionality critically controlled by process parameters with a respective period for a successful welding process. This paper deals with numerical modeling of heat generation during the plunge stage using the fully coupled thermomechanical Abaqus/Explicit package. Rapidly rise temperature is observed once plunging tool shoulder established contact with pipe surface. Frictional dissipation energy is prominent over plastic deformation during plunge phase. Numerical thermal response is correlated with literature experimental data. Â© 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.